Outsmarting the sociopath next door : how to protect yourself against a ruthless manipulator - Stout, Martha, 1953- (Harmony Books, 2020)
"From Dr. Martha Stout's influential work The Sociopath Next Door, we learned how to identify a sociopath. Now she tells us what to actually do about it. Using the many chilling and often heartbreaking emails and letters she has received over the years, Dr. Stout uncovers the psychology behind the sociopath's methods and provides concrete guidelines to help navigate these dangerous interactions"--